Guild‐level responses by mammalian predators to afforestation and subsequent restoration in a formerly treeless peatland landscape. Issue 5 (17th June 2020) - Hancock, Mark H.; Klein, Daniela; Cowie, Neil R.
Abstract : Afforestation of formerly open landscapes can transform mammalian predator communities, potentially impacting prey species like ground‐nesting birds. In Scotland's Flow Country, a globally important peatland containing many forestry plantations, earlier studies found reduced densities of breeding waders on open bogs, when forestry plantations were present within 700 m. One plausible explanation for this pattern is mammalian predation. We tested whether mammalian predator indices, based on scats (feces), differed between (1) open bog, forestry plantations, and former plantations being restored as bog ("restoration" habitats); (2) restoration habitats of different ages; and (3) open bogs with differing amounts of nearby forestry. We measured summer scat density and size over 14 years in 26 transects 0.6–4.5 km in length, collecting data during 93, 96, and 79 transect‐years in bog, forestry, and restoration habitats respectively. In forestry, scat density increased eightfold, reaching values 6 times higher than those of bogs. On open bogs with over 10% forestry within 700 m, scat densities were 2.9 times higher than on open bogs with less forestry nearby. Results support the hypothesis that mammalian predators might be responsible for the low densities of breeding waders close to forests, on adjacent open bogs. In restoration habitats, scat densities rose 6–10 years after felling but fell to levels similar to open bogs in older restoration habitats, supporting restoration management as a means of reducing mammalian predator activity/abundance. We urge caution around decisions to establish forestry plantations in open landscapes of high biodiversity importance.